Segi Sanitasi pada Pendaratan Ikan Tuna di Pelabuhan Perikanan Samudera Bungus, Sumatra Barat - Mustaruddin Mustaruddin; Eno Selomita; Thomas Nugroho; Sri Susanti Kartini (Institut Pertanian Bogor, 2022)
Clean and hygienic fish landings to meet sanitation requirements and guarantee the quality of the fish caught are an important part of the role of the fishing ports. However, it has not been done much at Bungus PPS, which was marked by the handling of fish quality that was not standardized, some unloading equipment and transportation facilities were rarely cleaned, and the environmental quality at the fish landing dock was not maintained. The study aimed to evaluate the quality control level of tuna fish, the performance of fish landing sanitation, and estimate the potential losses from neglected fish landing sanitation. The study used the scoring system, p control chart analysis, regression method, and profit/loss analysis. Organoleptically, the quality of tuna landed on Bungus PPS was at 7.50‒7.77 (fresh enough to fresh). The quality of tuna was still under control, with the value of upper control limit (UCL) = 0.220, central line (CL) = 0.07 and lower control limit (LCL) = 0.000. The sanitation performance of fish landings on PPS Bungus was around 3,45 (scale 1-5). Sanitation of fish handling (x) significantly affects the quality of tuna caught (y), which was indicated by the equation y = 0,1308x + 7,175. The sanitation conditions explained that 84.4% of the tuna caught were maintained. Potential losses from neglected landing sanitation were (a) the loss of the best-selling price of tuna and (b) the cost of nutrition consultation and disease management due to damage to the nutritional content of tuna. Keywords: bungus, tuna caught, fishing port, fish landing sanitation